ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA - Endri Endri (Economic Journal of Emerging Markets, 2008)
This research is aimed at analysing some factors that affect inflation rate in Indonesia during period 1997-2005. Using cointegration analysis and error correction model this research will investigate the relationship between independent variable and dependent variables in both short run and long run. In the long run, the monetary policy instrument (SBI rate), output gap and exchange rate have significant influence on inflation rate under floating exchange rate regime. In the short-run, the speed of adjustment of exchange rate is higher and significant for corrected to its long run equilibrium.Keywords: inflasi, efek transmisi, kointegrasi, error correction model